Some properties of nilpotent groups - Gaglione, A.M.; Lipschutz, S.; Spellman, D. (Algebra and Discrete Mathematics, 2009)
Property S, a finiteness property which can hold in infinite groups, was introduced by Stallings and others and shown to hold in free groups. In [2] it was shown to hold in nilpotent groups as a consequence of a technical result of Mal'cev. In that paper this technical result was dubbed property R. Hence, more generally, any property R group satisfies property S. In [7] it was shown that property R implies the following (labeled there weak property R) for a group G: If G₀ is any subgroup in G and G₀* is any homomorphic image of G₀, then the set of torsion elements in G₀* forms a locally finite subgroup. It was left as an open question in [7] whether weak property R is equivalent to property R. In this paper we give an explicit counterexample thereby proving that weak property R is strictly weaker than property R.